A family of lanthanide complexes with a bis-tridentate nitronyl nitroxide radical: syntheses, structures and magnetic properties. Issue 27 (18th June 2019) - Miao, Hao; Li, Hong-Qing; Shen, Fu-Xing; Wei, Hai-Yan; Wang, Bao-Lin; Wang, Xin-Yi
Abstract : A family of 2p–4f Ln III –radical complexes and 4f–2p–4f Ln III –radical–Ln III complexes were synthesized and characterized structurally and magnetically. Abstract : Eleven new lanthanide complexes based on a bis-tridentate nitronyl nitroxide radical NIT-Pm2Py (2-(4, 6-di(pyridin-2-yl)pyrimidin-2-yl)-4, 4, 5, 5-tetramethyl-4, 5-dihydro-1 H -imidazol-1-oxy-3-oxide), namely (NIT-Pm2Py)Ln(hfac)3 (Ln = Gd (1Gd ), Tb (2Tb ), Dy (3Dy ), Ho (4Ho ), Er (5Er ), Yb (6Yb )), [(NIT-Pm2Py)Ln2 (hfac)6 ]· x H2 O (Ln = Gd (7Gd ), Tb (8Tb ), Ho (10Ho ), x = 0.5 for7Gd and 1 for8Tb and10Ho ) and (NIT-Pm2Py)Ln2 (hfac)6 (Ln = Dy (9Dy ), Er (11Er )) were prepared and characterized. These complexes can be selectively prepared by controlling the reaction ratio of Ln(hfac)3 ·2H2 O to the radical ligand NIT-Pm2Py. Single crystal X-ray crystallographic analyses confirmed that1Gd –6Yb are isostructural 2p–4f Ln III –radical complexes, in which the NIT-Pm2Py radical acts as a terminal tridentate ligand chelating to one Ln III ion. On the other hand, 7Gd –11Er are isostructural 4f–2p–4f Ln III –radical–Ln III complexes with the NIT-Pm2Py acting as a bridging ligand between two Ln III ions.7Gd –11Er represent a rare family of complexes showing the NIT bridged 4f–2p–4f three-spin motif. Alternating-current (ac) magnetic susceptibility investigations revealed that complex6Yb exhibits field-induced frequency dependence, suggesting a possible field-induced single-molecule magnet behavior. Ab initio calculations were performed on all these complexes. The fitting of the magnetic susceptibilities of these complexes indicates weak antiferromagnetic coupling between the Ln III and NIT radical.